Digital Marketing Strategy as a Driver of Business Innovation in Global Market - Zahwa Noveliza Nur Safitri; Mohammad Afrizal Miradji; Dea Amirotul Ahlam (Proceeding International Conference on Digital Education and Social Science, 2024)
This article examines the role of digital marketing strategies as a driver of business innovation in the global market. In a competitive business environment, innovation is essential for company survival and growth. Digital marketing, which includes social media, SEO, and data analytics, enables companies to reach a wider audience and understand consumer preferences. This research identifies current trends in digital marketing and analyzes case studies of companies that have successfully implemented these strategies to drive innovation. Findings show that digital marketing integration not only improves efficiency but also contributes to the development of innovative products and services. The conclusion confirms that digital marketing strategies are key to achieving sustainable innovation in the global market.